BIOLOGICAL PRE -TREATMENT USE LOCAL WILD STRAIN OF LIGNOLYTIC FILAMENTOUS BACTERIA TO IMPROVE IN VITRO DRY MATTER DIGESTABILITY AND REDUCTION LIGNIN CONTENT OF LOW QUALITY ROUGHAGES . - & Al-Khateeb, Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study being performed at the central laboratory for graduate students Animal Resources Department / College of Agriculture / University of Baghdad/Aljadrea and in laboratory of applied microbiology Department, Food and Biotechnology Center /Directorate of Agriculture Research / Baghdad, Iraq. Wild strain of local ligninolytic bacteria of genus Streptomyces MS isolated from Iraq camel degrade feces was used to pre- treated of low quality roughages in in vitro fermentation. Roughages wheat straw (WS), corncobs (Cc), alfalfa hay (AH) was pre- treated with wild strain of genus Streptomyces MS. The results showed higher significant improvement (p<0.01) for in vitro dry matter digestibility (IVDMD %),in vitro Organic matter digestibility (IVOMD %) for most of roughages (WS Cc, AH). Moreover, greatest (p<0.01) improvement in(IVDMD,IVOMD %) was observed with pre-treated AH using Streptomyces MS prior of use for 21 days from 45 untreated to 67.07,67.08% treated, the smallest improving was observed (P<0.05) with WS from 20.78 to 30.22%. This result indicated that ability of Streptomyces MS to improve (IVDMD %) was significantly (P<0.05) affected by the roughages sources. Treated roughages with Streptomyces MS showed signiﬁcant reduction in lignin content (p<0.01).However, the highest (p<0.01) reduction in lignin content was shown in Cc pre-treated with Streptomyces MS(from 9.8 to 6.87%), while lowest (P<0.05)reduction in lignin content was shown in AH (from8.26 to 7.64%), These results support the possibility application of this wild strain of bacteria to improve low quality roughages in ruminants feed.